Subcapsular hepatic hematoma after endoscopic retrograde cholangiopancreatography: a case report and review of the literature - Segura Gago, Gino Perley (2022)
Endoscopic retrograde cholangiopancreatography (ERCP) is currently considered a diagnostic and therapeutic procedure in obstructive lesions of the biliary tract, especially choledocholithiasis and stenosis, as well as in pancreatic diseases in general. However, it is known the development of certain complications such as acute pancreatitis, acute cholangitis, cholecystitis among others of lower incidence within which the hepatic subcapsular hematoma takes relevance due to its high mortality. We present the case of a 52-year-old male patient who three hours after undergoing ERCP develops abdominal pain of sudden onset with significant reduction of hematocrit, and imaging study shows a hepatic subcapsular hematoma. He was initially managed conservatively a ge, subsequently showing residual descending contents by radiological follow-up.